Influence of Motivation on Workers' Performance at the University of Abuja - Duru, Innocent Uchechukwu; Eze, Millicent Adanne; Yusuf, Abubakar; Udo, Akpan Aaron; Saleh, Abubakar Sadiq (International Journal of Social and Administrative Sciences, 2022)
This study investigated the relationship between motivation and workers' performance at the University of Abuja. It utilized a descriptive research design. Both primary and secondary data were utilized in the study. Descriptive statistics and multiple regression methodology were employed on a sample of 337 workers’ obtained from 2145 workers through the stratified sampling method. The findings revealed that salary increase, promotions, allowances, regular timely salary and involvement in decision-making had a positive and significant effect on workers' performance at the University of Abuja. However, bonuses and fringe benefits had a negative and significant influence on workers’ performance. Furthermore, workers of the University of Abuja were not motivated by annual increments, recognition and supervision. The study recommends that the management of the University of Abuja should sustain their policies on salary increases, promotions, allowances, regular timely salary and involvement in decision making since they were yielding the desired outcomes. In addition, the policies of the University regarding annual increment, recognition and supervision should be strengthened and made to be effective. Furthermore, the policy on bonuses and fringe benefits should be reviewed as a result of their counterproductive nature.